Resistance To Change Of Forgetting Functions And Response Rates - Odum, Amy L (Society for the Experimental Analysis of Behavior, Inc., 2005)
This experiment examined the effects of reinforcement probability on resistance to change of remembering and response rate. Pigeons responded on a two-component multiple schedule in which completion of a variable-interval 20-s schedule produced delayed matching-to-sample trials in both components. Each session included four delays (0.1 s, 2 s, 4 s, and 8 s) between sample termination and presentation of comparison stimuli in both components. The two components differed in the probability of reinforcement arranged for correct matches (i.e., rich, p  =  .9; lean, p  =  .1). Response rates during the variable-interval portion of the procedure were higher in the rich component during baseline and more resistant to the disruptive effects of intercomponent food and extinction. Forgetting functions were constructed by examining matching accuracy as a function of delay duration. Baseline accuracy was higher in the rich component than in the lean component as measured by differences in the y-intercept of the forgetting functions (i.e., initial discrimination), rather than from differences in the slope of the forgetting function (i.e., rate of forgetting). Intercomponent food increased the rate of forgetting relatively more in the lean component than in the rich component, but initial discrimination was not systematically affected. Extinction reduced initial discrimination relatively more in the lean component than in the rich component, but did not systematically affect rate of forgetting. These results are consistent with our previous data suggesting that, as for response rate, accuracy and resistance to change of discriminating are positively related to rate of reinforcement. These data also suggest that the disruptability of remembering depends on the conditions of reinforcement, but the way in which remembering is disrupted depends on the nature of the disruptor.